An integrative action research (IAR) on developing the market using Facebook to generate leads and acquire new customers in an investment firm - Tinimbang, Lara C. (Animo Repository, 2021)
This action research addressed the lack of alternative marketing channel in a small investment firm, a situation that was aggravated by the social restrictions and business downturn under the Covid-19 pandemic. Having a marketing channel allows the company to promote its brand and financial investment products to potential customers. Because of this, the Business Development Team of ABC Corporation created a Facebook page and made use of Facebook advertisements to increase the number of accounts and volume booked in the company’s investment funds. The action researcher collaborated with peers in conducting two cycles of action research. The team used Ajuha and Loura’s 5P’s of Digital Marketing Framework to create an effective Facebook advertisement campaign. Other frameworks such as Segmentation and Targeting, and Customer Journey Framework were also used to further define the target market. After the two action research cycles, the results demonstrated that doing online marketing by having Facebook advertisements was indeed helpful in generating leads. The company was able to talk to potential clients who were looking for other investment outlets.